2020
DOI: 10.1634/theoncologist.2019-0605
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Assessment of Clinical Outcomes Among First-Line Sunitinib Patients with Clear Cell Metastatic Renal Cell Carcinoma (mRCC) by the International mRCC Database Consortium Risk Group

Abstract: Background. International Metastatic Renal Cell Carcinoma (mRCC) Database Consortium (IMDC) risk groups are important when considering therapeutic options for first-line treatment. Materials and Methods. Adult patients with clear cell mRCC initiating first-line sunitinib between 2010 and 2018 were included in this retrospective database study. Median time to treatment discontinuation (TTD) and overall survival (OS) were estimated using Kaplan-Meier analysis. Outcomes were stratified by IMDC risk groups and eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 20 publications
2
13
1
Order By: Relevance
“…Outcomes from this analysis were generally consistent with those from other studies [9][10][11][12][13][14][15], including analyses from other large databases [9,13,14]. A retrospective analysis of the 375 sunitinib-treated patients enrolled in the pivotal sunitinib versus interferon-α Phase III trial reported substantial differences in OS for patients of intermediate risk with 1 RF (IMDC, 28.2 months; MSKCC, 23.1 months) compared with patients with 2 RFs (IMDC, 16.3 months; MSKCC 16.7 months) [11].…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Outcomes from this analysis were generally consistent with those from other studies [9][10][11][12][13][14][15], including analyses from other large databases [9,13,14]. A retrospective analysis of the 375 sunitinib-treated patients enrolled in the pivotal sunitinib versus interferon-α Phase III trial reported substantial differences in OS for patients of intermediate risk with 1 RF (IMDC, 28.2 months; MSKCC, 23.1 months) compared with patients with 2 RFs (IMDC, 16.3 months; MSKCC 16.7 months) [11].…”
Section: Discussionsupporting
confidence: 86%
“…Notably, there was no statistically significant difference in OS for patients with 0 versus 1 RF stratified by IMDC. This suggests that patients with 1 IMDC RF (intermediate-risk group) have similar outcomes to IMDC favorable-risk patients, adding to the evidence that the intermediate group is heterogenous [9][10][11][12][13][14][15]24]. Consistently, OS was significantly longer for patients with 1 IMDC RF than for patients with 2 IMDC RFs.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…It is becoming increasingly apparent that the intermediate risk group (one or two risk factors) is heterogeneous [23,[36][37][38][39]. According to the IMDC and MSKCC models, the majority of patients present with intermediate risk, at 52 and 59% of patients, respectively [34].…”
Section: Discussionmentioning
confidence: 99%